2015
DOI: 10.1021/acs.jpcc.5b02169
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Bacteriophage and Laser Ablated Nanoparticle Complexes for Pathogen Detection

Abstract: We report the synthesis of colloidal nanoparticles, produced by the femtosecond laser ablation of a gold target, and their subsequent use in the formation of S. aureus phage−nanoparticle complexes for biodetection purposes. A detailed X-ray photoelectron spectroscopic analysis shows that the negatively charged nanoparticles that are formed interact with and subsequently internalize into the positively charged bacteriophages. These complexes render possible the specific detection of a single S. aureus bacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…When it comes to analysis of viruses and phages using XPS, very few studies exist and they mainly deal with applications in bioengineering using phages as a tool (Tawil et al, 2013;Tawil et al, 2015;Rho et al, 2018). To our knowledge, XPS has not previously been used in studies focusing on understanding the surface chemistry of viruses.…”
Section: Virus Surface Chemistrymentioning
confidence: 99%
“…When it comes to analysis of viruses and phages using XPS, very few studies exist and they mainly deal with applications in bioengineering using phages as a tool (Tawil et al, 2013;Tawil et al, 2015;Rho et al, 2018). To our knowledge, XPS has not previously been used in studies focusing on understanding the surface chemistry of viruses.…”
Section: Virus Surface Chemistrymentioning
confidence: 99%
“…The laser interaction with material in liquid medium yields direct synthesis of nanoparticles with distinct microstructures compared to other conventional synthesis techniques. ,, The recent development of controlled laser ablation synthesis and resulting microstructure of pure metals, alloys, composites, and biocompatible nanoparticles show the diverse potential applications of this method.…”
Section: Introductionmentioning
confidence: 99%
“…With the characteristics of distinct localized surface plasmon resonance (LSPR), gold nanoparticles (GNPs) and magnetic nanoparticles (MNPs) with sizes larger than 50 nm can scatter bright colored light under a common dark-field microscope, which allows the naked-eye observation of the detection event . With a high-resolution dark-field microscopy system, the multicolor of the scattered light of GNP can be directly photographed and has been applied in the detection of pathogen, biomarker molecules of Alzheimer and cancer cells via DNA-modified GNP. For pathogenic bacteria detection, GNP has been employed to enable methicillin-resistant Staphylococcus aureus (MRSA) to be observed under dark-field microscope . We also successfully developed a MNP-based dark-field assay for the detection of micron-sized pathogens such as Escherichia coli (∼1.5 μm) and Cryptosporidium parvum (∼5 μm) by constructing a wreath-like structure with MNPs of diameters 50 and 800 nm, respectively. , However, the MNP probe at 50 nm or larger size is ineffective to be employed to form a wreath-like structure for the pathogen with a size of only ∼200 nm because we found that only a few MNP probes at 50 nm on average attached to one target pathogen after incubation with target pathogens for 30 min or even longer.…”
mentioning
confidence: 99%
“…26−28 For pathogenic bacteria detection, GNP has been employed to enable methicillin-resistant Staphylococcus aureus (MRSA) to be observed under dark-field microscope. 29 We also successfully developed a MNP-based dark-field assay for the detection of micron-sized pathogens such as Escherichia coli (∼1.5 μm) and Cryptosporidium parvum (∼5 μm) by constructing a wreathlike structure with MNPs of diameters 50 and 800 nm, respectively. 17,18 However, the MNP probe at 50 nm or larger size is ineffective to be employed to form a wreath-like structure for the pathogen with a size of only ∼200 nm because we found that only a few MNP probes at 50 nm on average attached to one target pathogen after incubation with target pathogens for 30 min or even longer.…”
mentioning
confidence: 99%